Primary School Teachers' Experiences in the Identification of Gifted Students and Nominating Them to Science and Art Centers - Erol, Mustafa; Gedik, Osman; Demirtas, Berat (ANKARA UNIV, FAC EDUCATIONAL SCIENCES, 2023)
Introduction: This study aims to examine the experiences of primary school teachers in the identification of gifted students and nominating them to science and art centers. Method: This research was carried out within the scope of phenomenology design, one of the qualitative research designs. The research study group was determined by the criterion sampling method, one of the purposeful sampling methods. The research study group consisted of 15 primary school teachers working in Istanbul. The study data were obtained through semi-structured interview forms developed by the researchers and personal interviews conducted with the study group. The data were analyzed by content analysis. Researcher triangulation was used in the analysis of the data. To minimize data loss, the data were recorded with a voice recorder. Findings: According to the study's findings, it was determined that the classroom teachers took into account the students' cognitive, affective, and social characteristics while identification them with giftedness and made observations depending on the process. Discussion: Although many features are used to identify gifted students when the relevant literature is examined, it has been determined that cognitive features are frequently used in the identification of gifted students.
Keywords: Gifted students; primary school teachers; science and art centers; experience; TALENT DEVELOPMENT; EDUCATION; MOTIVATION; Education & Educational Research